ANALISIS STRATEGI MEDIA RELATIONS PT PARAGON TECHNOLOGY & INNOVATION DALAM MEMBANGUN CORPORATE NARRATIVE - Feyza Syifa Ashila; Agus Naryoso; Joyo Nur Suryanto Gono (Interaksi Online, 2023)
The background of this research is based on the fact that although PT Paragon Technology & Innovation has successful cosmetic brands, such as Wardah, Emina, and Make Over, this company is little known in the public and has a lack of online media coverage, which reflects an unequal comparison between brand popularity and understanding of the company itself. This research analyzes PT Paragon Technology & Innovation's media relations strategy in building its corporate image. This research adopts a post-positivism paradigm with a case study approach and pattern-matching analysis techniques based on Stakeholder Theory, Impression Management Theory, the corporate narrative concept and the publicity concept. The main focus is the Corporate Communication division of PT Paragon Technology & Innovation, which plays a role in media relations. Primary data was obtained through interviews, observation, and document analysis, while secondary data was used as support. The validity of the data is ensured through the criteria of credibility, transferability, dependability, and certainty. The research results show that PT Paragon Technology & Innovation implements a comprehensive media relations strategy in building a corporate narrative. They build strong relationships with the media through pitching relevant to the audience and company narrative. Implementing the media relations program continuously includes media amplification, press conferences, media visits, media tours, media collaboration, media gatherings, and the Media Journalism Fellowship. The research suggestion is for PT Paragon Technology & Innovation to increase the effectiveness of media relations by conducting briefings related to the intensity of mention of the name PT Paragon Technology & Innovation in reporting to the media, providing news material with factual data accompanied by history or milestones regarding PT Paragon Technology & Innovation. In this way, PT Paragon Technology & Innovation can better overcome the imbalance between brand popularity and understanding of the company itself.